I controlimiti al primato del diritto dell'Unione europea nel dialogo tra le Corti - Pellegrini, Daniele (Premio Ricerca «Città di Firenze», 2021)
The book challenges the 'counter-limits' (controlimiti) doctrine devised by the Italian Constitutional Court, in the light of the developments that have taken place within the EU framework over the last decades. The subject matter becomes the looking glass through which the author verifies 'whether' and 'to what extent' the judicial cooperation system based on the mechanism of preliminary ruling under article 267 TFEU is suitable to allow a reassessment of the 'counter-limits review' and, more generally, capable to ease the settlement of constitutional conflicts between national and EU legal orders. A thorough examination of the perspectives involved helps to prove the existence of a 'judicial dialogue' as to the question of constitutional limits to the primacy of EU law, and to deepen the decision-making process of EU Member States' Constitutional Courts when fundamental constitutional principles are at stake. Leveraging on this background, some recent rulings are investigated to verify, on a case-law basis, the balancing of values carried out by national and EU Courts.